Conversion of anilines to chiral benzylic amines via formal one-carbon insertion into aromatic C–N bonds - Lei Li (Nature Portfolio, 2020)
Atom insertion into aromatic carbon-nitrogen (C-N) bonds is useful for the synthesis of nitrogen-containing molecules, but challenging due to the inert nature of these bonds. Here, the authors report one-carbon insertion into aromatic C-N bonds to directly convert anilines to chiral benzylic amines.